Increasing the studentsâ€™ speaking ability in giving suggestions and advice by the using of "whip around" strategy - Atalisi Zalukhu; Mitra Gusmeni Hia (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
Speaking is the ability to convey information or expressing to convey everything in their mind orally. Therefore, it is important for students to master speaking in their daily life because through speaking students can express their ideas, feelings, opinions, and knowledge. There were some problems faced by the students in speaking in Second grade of SMP ADHYAKSA namely: the students lacked vocabularies, and the students are not able to deliver their suggestion and advice. Therefore, to overcome the problems, the researcher conducted this research by using â€œWhip Aroundâ€ Strategy in second grade of SMP ADHYAKSA. The purpose of the research is to increase the studentsâ€™ ability in speaking by using whip around Strategy at the second grade of SMP adhyaksa. To achieve the purpose, the researcher conducted CAR Method. The result of the data in Cycle I showed the average of studentsâ€™ value was 60, the maximum score was 78 and the minimum score was 41. While in Cycle II 20 students (100%), the student got the maximum score was 83 and the minimum score was 75. From the result o the research, it can be concluded that â€œWhip Aroundâ€ Strategy increases the studentsâ€™ speaking ability in second grade of SMP adhyaksa. Finally, the researcher suggested all English teacher to use this strategy in teaching speaking skill because â€œWhip Aroundâ€ Strategy is effective to increase the studentsâ€™ ability in speaking. â€œWhip Aroundâ€ Strategy encourages the studentsâ€™ to express their suggestion and advice orally and engaged the student high motivation during the teaching and learning process.Â